(untitled) (Boletin Médico de Postgrado, 2022)
Work accidents represent a world public health problem. In Venezuela, a legal framework has been built that provides tools for company’s occupational health and safety management systems for the prevention of damage to occupational health. With regard to occupational diseases, there is an updated normative framework adjusted to the Organic Law of Prevention, Conditions and Work Environment (LOPCYMAT), however there is no INPSASEL technical rules on work accidents, leaving the COVENIN 474: 1997 standard in force, prepared and published prior to the reform of the LOPCYMAT in 2005, which brings disagreements between the vision of said Law and the requirements of INPSASEL as the governing body, thus making the approach of work accidents difficult in the operation of management systems in work centers. The present investigation framed in the modality of special project, had the aim to elaborate a guide for monitoring, surveillance and investigation of work accidents in manufacturing industries in Barquisimeto-Lara. The study was developed in four phases: diagnosis of the need to prepare the guide, design, validation and edition of the guide. Its elaboration was necessary to guide the actors of the occupational health and safety management systems in the performance of proper monitoring, surveillance and investigation of occupational accidents.